A STUDY ON CUSTOMER PERCEPTION TOWARDS E-BANKING SERVICES IN KOVILPATTI THALUK (International Journal of Food and Nutritional Sciences, 2022)
With the introduction of e-banking services in India, banking operations have been improved and operating costs have gone down. It encourages clients to conduct business online, through mobile banking, POS systems, and other means. This study looks at Kovilpatti's consumer perceptions of and preferences for using online banking services, as well as those who don't. This survey shows that the benefits of using electronic banking services are convenience, dependability, safety, time savings, trust, privacy, and speed are the main drivers. Security issues, a lack of trust, and knowledge deficiencies are revealed by parallel findings on the opposing side.IntroductionThe practice of banking as we know it now first appeared in India during the latter two decades of the 18th century. One of the first banks was the Bank of Hindusthan, which was founded in the same year. However, there have been several modifications to banking systems and the services they offer in the 20th century.An emerging trend in banking services is e-banking. E-banking services are part of the concept of technological advancement in the world. In e-banking, a customer can make information requests and complete banking tasks including checking their account balance, transferring money, paying bills, recharging their phones, requesting a chequebook, etc. using a telecommunications network without going to the bank.